Hubungan Antara Beban Kerja Dan Pengalaman Kerja Dengan Kinerja Perawat di Ruang Rawat Inap RS Premier Surabaya - Pristiawati , Aninda Ika; Ernawati, Dwi (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: to analyze the correlate between workload and worked experience with nurse performance in the inpatient room of Premier Hospital Surabaya.Methods: This article used correlation analysis by cross sectional approach. The population is 51 nurses in the inpatient room at Premier Hospital Surabaya use Proportionate Stratified Random Sampling technique. Independent variable of this study are workload and worked experience, assessed by questionnaire. Variabel dependent of this study is the performance of nurse with assessed by questionnaire. Data analysis of this study use spearman rho p. = 0,05.Results: Results of this study, shows that there is no correlation between workload and worked experience with nurses performance, with results of workload analysis p = 0.053 > α = 0.05 and worked experience p = 0.137 > α 0.05.Conclusion: Premier Hospital Surabaya can maintain and improve the performance of nurses, but must still care with workload level which feel the nurses. The expected that there are an evaluation of workload, training which can add the skills and work experience of nurses, so good performance which doing the nurses can be maintained and nurses can give the good service to patients.